The Value of Brand Image and Design in Seasonal Packaging - Lisińska-Kuśnierz, Małgorzata (Studia Oeconomica Posnaniensia, 2017)
Specific brand image and design associated with special occasions pertains to the so called seasonal packaging of products. The packaging of such goods can boast completely new designs, new shapes or seasonal graphics. Seasonal packaging might also be understood as slightly modified standard packaging with additional ornamental elements such as a cardboard cover with a holiday theme, supplements or a decorative bow emphasizing the idea of a gift. The aim of this paper is to present the results of a comparative study of consumer expectations relative to seasonal packaging and behaviours associated with the selection and purchase of products in such packaging as well as the image evaluation of these packages. The research material consisted of special gift chocolate products on offer before Christmas with holiday themes on product packaging, and without them. The findings of the study allow determining consumer preferences in terms of products' packaging design, selection of colours and graphic elements to be used that are strongly associated with the Christmas season. The confrontation between the consumers' expectations regarding the visual aspects of seasonal packaging and their purchasing choices of chocolate products as Christmas gifts showed the importance of brand recognition and its determining role as opposed to holiday graphics or unusual packaging shape.